1986
DOI: 10.1073/pnas.83.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a chemically defined serum- and protein-free medium for growth of human peripheral lymphocytes.

Abstract: A chemically defined, protein-free medium (designated CFBI 1000, where CFBI = Clayton Foundation Biochemical Institute) that supports human peripheral lymphocyte proliferation has been developed. This medium allows exploration of individual metabolic differences by varying the medium composition as well as providing a base to explore further the mechanisms of lymphocyte activation in a system initially free of added macromolecular species other than mitogen. The peripheral blood lymphocyte is an ideal system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The functional assessment of intracellular deficiencies of micronutrients was performed by the lymphocyte transformation assay developed by Shive et al(19–24). In this procedure, blood is collected in two 10ml cell preparation tubes (Becton Dickinson) containing sodium citrate and ficoll hypaque.…”
Section: Methodsmentioning
confidence: 99%
“…The functional assessment of intracellular deficiencies of micronutrients was performed by the lymphocyte transformation assay developed by Shive et al(19–24). In this procedure, blood is collected in two 10ml cell preparation tubes (Becton Dickinson) containing sodium citrate and ficoll hypaque.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we made an observation that IMDM is inferior to a-medium for serum-free culture of human marrow progenitors plated at low cell concentrations. Recently, Shive et al [17] described a chemically defined, serum-and protein-free medium (CFBI 1OOO) for suspension culture of human peripheral lymphocytes. The concentrations of individual components of CFBI 1 ,OOO reflect minimal effective concentrations and are significantly lower than those of IMDM and a-medium.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte growth in culture media to which individual micronutrients are added or deleted and compared to the lymphocyte growth in optimal culture media are determined. In the study reported here, the influence of the EMF is the difference between samples taken before and after exposure to the EMF (Tu et al, 1994;Shrive et al, 1986;Boerner, 2001;Shive, 1988). Thus, each individual serves as his/her own control as the lymphocytes were cultured from the patients blood taken before and after exposure to the EMF of the THERAMAG device.…”
Section: Spectracell Studiesmentioning
confidence: 99%